Cryo‐electron tomography—the cell biology that came in from the cold. Issue 17 (2nd August 2017) - Wagner, Jonathan; Schaffer, Miroslava; Fernández‐Busnadiego, Rubén
Abstract : Cryo‐electron tomography (cryo‐ET) provides high‐resolution 3D views into cells pristinely preserved by vitrification. Recent technical advances such as direct electron detectors, the Volta phase plate and cryo‐focused ion beam milling have dramatically pushed image quality and expanded the range of cryo‐ET applications. Cryo‐ET not only allows mapping the positions and interactions of macromolecules within their intact cellular context, but can also reveal their in situ structure at increasing resolution. Here, we review how recent work using cutting‐edge cryo‐ET technologies is starting to provide fresh views into different aspects of cellular biology at an unprecedented level of detail. We anticipate that these developments will soon make cryo‐ET a fundamental technique in cell biology. Abstract :